OPTIMALlSASI BATIK TRADISIONAL SURAKARTA IMPLEMENTASINYA PADA ASESORIS BERBASIS TRADISI SEBAGAI UPAYA PENGOKOHAN BUDAYA LOKAL SURAKARTA DI ERA GLOBAL - Sunarmi Sunarmi (Gelar : Jurnal Seni Budaya, 2010)
This research is entitled "Optimizing Tradisional Batik of Surakarta: its Implementation to Traditional Based Accessories as an Effort to Strengthen local Culture of Surakarta in the Globalization Era".  The research aims at analyzing and realizing traditional batik of Surakarta as a traditional-based interior element to support the district tour and to strengthen the local culture in the era of  globalization. The problems of this research are as follows: 1) to optimize the utilization of batik of Surakarta as a souvenir of the district tour; 2) to make the craftsman more sensitive to the cultural  richness in Surakarta as a work of design and 3) to recommend to the authority. The activities will be carried out for two years. The results of the research in the first year were the identification of  the forms of batik of Surakarta and the map of design offered. The existence of batik should be developed and the concept of the development should be based on batik characteristics, especially  the element of batik surface design, namely, batik motif and batik as a technique. There are five activities in the second stage, that is, the experiment for developing, training for the craftsman, try out of the result, the completion of batik developing concept, and the recommendation.The strategy used was actively programmed by making use of modality: hearing, visual, kinesthetic. Brainstorming is used as a response to the strategy design. Try out is carried out using drill method and assistance. The result of the experiment is the combination of parang batik with tenun lurik (hand-woven cotton with a stripped pattern) which has shortcomings and advantages.  The advantages are that the innovative design of the surface appearing as tenun lurik with batik motif made by batik technique is easily adjusted to the need for interior elements; the cloth used  is hand-woven cotton with a stripped pattern; the natural dye is that is used for batik which is environment-friendly. The shortcomings of this design are as follows: the cost is higher than that of traditional batik; to combine batik with tenun lurik needs substance used to remove the colour of tenun lurik and it takes a long time. To make the cost cheaper so that it is affordable for anyone, we need to make plans for the cloth size and the dyeing both of which should be considered at the time of weaving process. Due to that the activities should be supported by all sides especially the financier.Key words: Batik, tenun lurik, elements interior, and inovation